A study on role of DSA in intracerebral vascular anomaly comparison with computed tomography angiography/magnetic resonance angiography - Halder, Soumitra; Mondal, Dilip Kumar; Sharmistha Bhattacherjee; Datta, Panchali; Daksit, Debashis; Datta, Sumit (Asian Journal of Medical Sciences, 2022)
Background: Brain imaging techniques provide the ability to noninvasively map the structure and functions of the brain. Brain vascular malformation mainly affects people in the 5th decade followed by 4th and 3rd decade. Aims and Objectives: The aim of the study was to compare the diagnostic supremacy of computed tomography angiography (CTA)/magnetic resonance angiography (MRA) and Digital subtraction angiography (DSA) for the detection of intracranial vascular anomalies. Materials and Methods: An observational descriptive study with cross-sectional design was performed among 50 patients of both sexes undergoing DSA test at Medical College and Hospital, Kolkata with acute stroke syndrome or any other symptoms suggesting intracranial vascular lesion, who were investigated with one or more index tests and a reference standard diagnosed by computed tomography (CT) or MR scanning or other parameters. DSA served as the standard of reference for presence of intracranial vascular anomalies. Results: Out of the 50 patients included in the study, 41 were diagnosed with vascular malformations by DSA. Moya moya disease was diagnosed in three and distal AV fistula in six patients. In the 41 patients with vascular malformations, CTA could correctly identify 17 (41.5%) cases whereas MRA could identify 73.2% cases. Conclusion: DSA can be used for both diagnostic and interventional angiography. Its high spatial and temporal resolution have maintained DSA as a very important tool. The study reveal DSA is more superior to accurate angioarchitectural delineation of different intracerebral vascular malformation.